2015
DOI: 10.1002/eat.22397
|View full text |Cite
|
Sign up to set email alerts
|

Structural hippocampal alterations, perceived stress, and coping deficiencies in patients with anorexia nervosa

Abstract: In sum, our study provides the first-available evidence that perceived stress in patients with AN could be related to hippocampal volume. Our results may contribute to a better understanding of the pathophysiology of AN and, therefore, help to improve the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 25 publications
9
23
0
Order By: Relevance
“…Here we find that this pattern remains after weight restoration. While hippocampal volume abnormalities have been demonstrated in AN (Burkert, Koschutnig, Ebner, & Freidl, 2015), such abnormalities may not be associated with changes in cognitive function (Connan et al, 2006). Thus a host of neural changes may accompany AN, but it is critical to link neural changes to relevant cognition and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Here we find that this pattern remains after weight restoration. While hippocampal volume abnormalities have been demonstrated in AN (Burkert, Koschutnig, Ebner, & Freidl, 2015), such abnormalities may not be associated with changes in cognitive function (Connan et al, 2006). Thus a host of neural changes may accompany AN, but it is critical to link neural changes to relevant cognition and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one previous study has investigated HS in AN patients (Burkert et al, 2015). Adult AN patients who had been ill for several years were found to have a significant reduction in the fimbriaa white matter bundle projecting along the anterior-posterior axis of the hippocampus (Burkert et al, 2015), and an increase in the size of the hippocampal fissure -the "ventricle" of the hippocampus.…”
Section: Introductionmentioning
confidence: 96%
“…Volume reduction of the hippocampus formation has been reported in several studies in both adults (Burkert et al, 2015;Chui et al, 2008;Connan et al, 2006;King et al, 2015;Mainz et al, 2012). The formation of the hippocampus is well known for its involvement in learning and memory, but also plays an important role in emotional regulation (Fanselow and Dong, 2010).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to its complexity, the neurobiology of anorexia nervosa is unknown, but studies using magnetic resonance imaging showed hippocampal volume reduction [36]. The hippocampus is involved in spatial learning, cognition, and regulation of anxiety [7].…”
Section: Introductionmentioning
confidence: 99%